Typology of geosystems of Belarusian Polesie - Chervan, Aliaksandr N.; Davidovich, Yury S. (Journal of the Belarusian State University. Geography and Geology, 2024)
The principles and methodology of the typology of geosystems of the Belarusian Polesie based on geoinformation spatial analysis of the soil cover structure are outlined. An algorithm for identifying geosystems through the composition and structure of soil combinations using Belarusian nomenclature and approaches to soil classification is presented. The justification for the selected nomenclature of soil combinations is given, the hierarchical grouping of geosystems of the Polesie is considered taking into account morphometric, geomorphological, hypsometric, lithological and other characteristics. Techniques for using the contrast scale and a modified assessment of the dissection of the soil cover structure with the use of automated map-metric analysis are indicated, which made it possible to create an integrated holistic view of the geosystems of Polesie region. On the territory of Belarusian Polesie 25 variants of natural systems have been identified, differentiated into 101 soil mesocombinations depending on orographic, geomorphological, hypsometric and lithological conditions, which together constitute 68 % of the geographical environment diversity of the republic assessed by the soil cover structure. Geosystems are considered as territorial units in areas of environmental management in accordance with the functional types of administrative districts of Belarus. An explication of the areas of geosystems in the region is presented. The feasibility of using Earth remote sensing data in determining the state of geosystems of Belarusian Polesie has been assessed.
Keywords: geosystem; Belarusian Polesie; soil combination; soil cover structure; Earth remote sensing; territorial planning; soil-resource potential